An Automatic Load Detector Design to Determine the Strength of Pedestrian Bridges Using Load Cell Sensor Based on Arduino - Kurnia Paranita Kartika Riyanti; Ismail Kakaravada; Abdussalam Ali Ahmed (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The basic requirement that must be met in the construction of a bridge is the resilience. This resilience depends upon the supporting of bridge when the load that passes over the bridge. Loading condition on bridge is generally in the form of dynamic which ​​can vary according to crossing conditions on it. This reason validates in difficulties in estimation the lifetime of the bridge. In order to maintain the good condition of the bridge the estimation of overloading condition and its effects of over loading on bridge need to evaluate to keep the bridge durable for that a bridge load measuring detector is needed. The aim of this research is to design an automatic load detector to test the strength of the bridge at dynamic loading conditions. The load detector designed through an Arduino-based load cell sensor. The detector equipped with I2C LCD display mechanism which can display the load on bridge and buzzer switch with warning alarm which can alert when bridge is over loaded. The total sensor mechanism was tested on a miniature wooden bridge with selected loads. During testing, the detector load cell sensors placed at the bottom of the bridge surface with a running load, the readings are considered recorded for several load cells at dynamic loading conditions. In the research work was carried out on the bridge using various load ranges from 100 grams to 25 kilograms on load cells at various positions. From the experimentation it has been noticed that, the load cell has displayed the smaller value as compared with the actual value due to the load distribution over the bridge structure. From the experimental data it is noticed that the average error rate 4.67%, hence the developed sensor system more suitable for practical application to evaluate the damage of the bridge. It also concluded that, the detector is more effective in evaluation of dynamic loading condition to prevent damage of bridge.